Molecular Dynamics Simulations for Plasma‐Surface Interactions. Issue 1 (7th September 2016) - Neyts, Erik C.; Brault, Pascal
Abstract : Plasma‐surface interactions are in general highly complex due to the interplay of many concurrent processes. Molecular dynamics simulations provide insight in some of these processes, subject to the accessible time and length scales, and the availability of suitable force fields. In this introductory tutorial‐style review, we aim to describe the current capabilities and limitations of molecular dynamics simulations in this field, restricting ourselves to low‐temperature non‐thermal plasmas. Attention is paid to the simulation of the various fundamental processes occurring, including sputtering, etching, implantation, and deposition, as well as to what extent the basic plasma components can be accounted for, including ground state and excited species, electric fields, ions, photons, and electrons. A number of examples is provided, giving an bird's eye overview of the current state of the field. Abstract : In this review, we describe the current capabilities and limitations of molecular dynamics simulations of plasma‐surface interactions. We pay specific attention to the simulation of the various fundamental processes, as well as to what extent the basic plasma components can be accounted for. We also provide a number of examples, giving an bird's eye overview of the current state of the field.